An Analysis of SWOT Processing of Crab (Portunus pelagicus) in Watolo, Mawasangka Subdistrict, at The Central Buton Regency - Sabrin, Muhammad; Tamrin, Tamrin; Syukri, Muhammad (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2020)
Micro Business is one of the Micro Enterprises in managing Crab Crab located in Watolo Subdistrict, Mawasangka Subdistrict, Central Buton Regency, this Micro Business produces fishery products in the form of Crab Crab Meat (shellless crabs). The purpose of this study is to know the internal and external factors of Micro Enterprises and to know the strategies for developing Micro Enterprises that are competitive. This study uses the SWOT analysis method. With the SWOT analysis, it can produce several Â alternative strategies in making good decisions to run, so that it can determine the competitive strategy of Micro Business development. The results of this study found that the strength of 1.51, weakness 1.74, opportunities of 0.96 and threats 1.87. The curvaceous diagram shows that KAYUJUM Micro Enterprises are on the Defense path where KAYUJUM Micro Enterprises can try to minimize existing weaknesses and avoid the threat that will occur.